A single-layer molybdenum disulfide high-flux water-ion separation membrane based on grain boundary engineering, a preparation method and applications thereof
Patent Information
- Application Number
- CN202611455797.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]针对现有二维分离膜孔径不可控、通量-截留权衡、难以大面积制备的缺陷,提供一种晶界工程调控单层MoS2分离膜及其制备方法:通过籽晶定向对齐实现晶粒仅存在0°/60°两类取向,在镜像孪晶晶界大量生成筛分尺寸适配的八元环(8-MR)孔道;通过调控形核密度精准控制晶粒尺寸,线性提升8-MR孔密度,打破传统膜通量与选择性此消彼长的矛盾,实现高通量、超高离子截留、长周期稳定运行,可用于海水淡化、重金属纳滤、硼去除等水处理场景
筛分性能突破:8-MR亚纳米孔道实现尺寸筛分主导分离机制,打破传统高分子膜、二维膜“通量-截留”权衡;晶粒细化可同步提升水渗透通量与离子选择性。
Smart Images

Figure CN122998994A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of two-dimensional material separation membranes, seawater desalination, and nanofiltration water treatment technology. Specifically, it relates to a two-dimensional separation membrane and its preparation process that precisely generates eight-membered ring sieve channels at grain boundaries by directionally controlling the orientation and grain size of monolayer molybdenum disulfide crystal domains. Background Technology
[0002] Two-dimensional materials, due to their atomically thin thickness, can theoretically achieve both ultra-high water flux and ion retention simultaneously, making them a core candidate material for next-generation desalination membranes. Existing technologies for preparing nanoporous two-dimensional membranes mainly fall into two categories: Post-processing pore-forming methods: ion / electron irradiation, plasma etching, chemical etching. These methods are difficult to uniformly control pore size and pore density over a large area. The pore size distribution is wide, and the film contains a large number of ultra-large defect pores and ineffective micropores. There is an inherent trade-off between flux and retention performance, and it is impossible to achieve both high permeability and high selectivity. Grain boundary native defect pore creation: directly using natural defects at grain boundaries as sieving channels during the CVD growth of two-dimensional materials. Existing polycrystalline molybdenum disulfide thin films have randomly oriented grains, with grain boundaries dominated by seven-membered ring (7-MR) defects. The pore size of the seven-membered rings is too small, preventing water molecules from penetrating and thus lacking separation capability. The few randomly generated eight-membered rings (8-MR) are extremely rare and disordered, resulting in extremely poor film flux and making them unsuitable for industrial application.
[0003] Existing technologies suffer from three major bottlenecks: ① inability to generate large-area, high-proportion sub-nanometer sieve pores with precise dimensions; ② inability to simultaneously control grain boundary density (pore density); and ③ poor membrane stability, making it difficult to scale up to wafer-level large-area continuous thin films. Therefore, there is an urgent need for a complete process capable of precisely directionally constructing eight-membered ring grain boundary channels, controllably adjusting pore density, and preparing high-performance water ion separation membranes over large areas. Summary of the Invention
[0004] To address the shortcomings of existing two-dimensional separation membranes, such as uncontrollable pore size, flux-retention trade-off, and difficulty in large-area fabrication, this paper proposes a grain boundary engineering-controlled monolayer MoS2 separation membrane and its preparation method. By aligning seed crystals, the membrane exhibits only two orientations: 0° and 60°. This generates a large number of 8-membered ring (8-MR) channels with suitable sieve size at the mirror twin grain boundaries. By precisely controlling the nucleation density, the grain size is precisely controlled, linearly increasing the 8-MR pore density. This breaks the traditional trade-off between flux and selectivity, achieving high flux, ultra-high ion retention, and long-term stable operation. It can be used in water treatment applications such as seawater desalination, heavy metal nanofiltration, and boron removal.
[0005] This invention provides a grain boundary-engineered modified monolayer molybdenum disulfide water-ion separation membrane, characterized in that it comprises a functional layer and a substrate layer composited together. The functional layer is a continuous monolayer molybdenum disulfide thin film. Within this film, all molybdenum disulfide grains exhibit only two lattice orientations: 0° and 60°, with each grain forming a 60° angle with the others. Adjacent grains form mirror twin grain boundaries, and the dominant defect at these boundaries is an 8-4 composite octagonal ring channel. The substrate layer is a porous membrane material or an anode material, and the continuous monolayer molybdenum disulfide film is attached to the substrate layer by membrane transfer.
[0006] Furthermore, the proportion of octagonal ring sieve pores in the continuous monolayer molybdenum disulfide film to all permeable channels is ≥97%, and the pore size is 4.2 Å × 2.4 Å.
[0007] Furthermore, the average grain area of the continuous monolayer molybdenum disulfide thin film is controllable within the range of 0.25–444.37 μm. 2 .
[0008] Furthermore, the porous membrane material is an inorganic porous membrane, an organic porous membrane, or an inorganic-organic porous membrane, wherein the organic porous membrane is preferably a porous polycarbonate.
[0009] Furthermore, the anode material is an alumina anode material.
[0010] On the other hand, the present invention provides a method for preparing the aforementioned monolayer molybdenum disulfide water-ion separation membrane, characterized by comprising the following steps: Step (1): Substrate pretreatment: α-Al2O3(0001) sapphire wafers were selected as the growth substrate. The tube furnace was divided into a sulfur source temperature zone of 145~175℃ and a thin film growth temperature zone of 750~800℃, with argon gas oxygen-free protection throughout the process. Step (2): Low-temperature seed crystal orientation and alignment: The sulfur source temperature zone is heated to 145~175℃, and the film growth temperature zone is heated to 750℃. MoO3 powder is used as the molybdenum precursor. The sulfur source in the sulfur source temperature zone is introduced into the film growth temperature zone along with argon gas. The S / Mo atomic ratio is >1. In the film growth temperature zone, the molybdenum precursor reacts with sulfur vapor in situ to generate MoS2 nano-seed crystals. The temperature is maintained at 750℃ for 15~40min, and the high S / Mo atomic ratio is maintained. The MoS2 nano-seed crystals spontaneously rotate and align to 0° or 60° lattice orientation. Step (3): High-temperature continuous film growth: After the MoS2 nanoseed crystals are aligned, the temperature of the sulfur source temperature zone remains unchanged. The film growth temperature zone is heated to 800℃ and kept at a constant temperature for 60~120 min. During the constant temperature growth process, the nucleation density and MoS2 grain size are controlled by adjusting the temperature of the sulfur source temperature zone between 145~175℃. Adjacent grains are spliced together along armrest-shaped edges, forming stable 8-4 composite octagonal ring channels at the grain boundaries; Step (4): Cooling and collecting MoS2 monolayer film: After the reaction was completed, the film was cooled to room temperature under an argon atmosphere to obtain a uniform continuous monolayer molybdenum disulfide film with a diameter of 5.08 cm. Step (5): Wet transfer to prepare composite membrane: Polydimethylsiloxane (PDMS) is used to help peel off the single-layer MoS2 film and transfer it to a porous membrane material or anode material support substrate; when the support substrate is an anode material, the substrate composite membrane is matched with interface polymerization to seal the pores and eliminate pinhole defects, and the finished separation membrane is obtained.
[0011] Furthermore, in step (3), the relationship between the sulfur source temperature and the MoS2 grain size is adjusted as follows: when the sulfur source temperature is 175℃, 0.25μm MoS2 grains are prepared. 2 Small-grained thin films with a thickness of 444.37 μm were prepared when the sulfur source temperature was 145 °C. 2 Large-grain thin films.
[0012] Furthermore, the anode material mentioned in step (5) is an alumina anode (AAO) material, and the specific process for interface polymerization and sealing of the substrate composite film is as follows: (5.1) Pretreatment before membrane preparation: Fix the MoS2 / AAO composite membrane after PDMS-assisted transfer to the dead-end filter fixture, ensuring that the single-layer MoS2 functional layer faces upward and the AAO porous substrate faces away; first, introduce isopropanol to wet the AAO pores, then introduce deionized water to fully replace the organic solvent in the pores, remove air bubbles in the pores, and drain the free water droplets on the membrane surface at room temperature, leaving only the adsorbed aqueous phase in the AAO pores; (5.2) Aqueous phase amine monomer filling: Inject an aqueous solution from the AAO substrate side. The aqueous phase consists of 0.5-2 wt% m-phenylenediamine (MPD) and 0.1 wt% neutralizing agent triethylamine. The aqueous solution is continuously soaked for 10 min to allow the polyamine monomers to be fully adsorbed and stored in the porous channels of the AAO. The composite membrane is then removed, suspended vertically, and the residual aqueous phase on the surface of MoS2 is thoroughly wiped off, leaving only the amine monomers inside the channels. (5.3) Interfacial polymerization reaction: Slowly inject an organic phase solution into one side of the MoS2 functional layer. The organic phase composition is 0.05~0.2 wt% trimesoyl chloride (TMC) and n-hexane solvent, completely immersing the surface of the MoS2 film. Allow the reaction to stand for 30~60 s. In the AAO channels, m-phenylenediamine diffuses upward along the pinhole defects and crosslinks in situ with the surface trimesoyl chloride inside the pinholes to form a dense polyamide, thereby sealing the AAO channels. (5.4) Residual liquid washing to terminate the reaction: Pour out the organic phase, and use pure hexane to quickly rinse the surface of MoS2 to remove unreacted acyl chloride monomers; then use a large amount of deionized water to rinse both sides of the membrane to remove residual free amine in the pores; (5.5) Thermosetting crosslinking: The cleaned composite film is placed in an oven at 60~70 ℃ for 8~12 min to promote deep crosslinking of polyamide molecular chains; (6) Post-treatment: After cooling to room temperature, soak in deionized water for 2 hours to remove uncrosslinked small molecules, complete the sealing, and obtain a C-MoS2 / AAO high-pressure nanofiltration composite membrane with no leakage defects and only retaining 8-MR sieve channels.
[0013] Furthermore, it also includes step (6) quality inspection process: the prepared composite membrane is placed in humid and hot air at 60% relative humidity and 100℃ for annealing for 1 h, and the pollutants are enriched along the grain boundary. The grain size and grain boundary length are statistically analyzed by scanning electron microscopy, the octagonal ring pore density is calibrated, and batch rapid quality inspection is achieved.
[0014] The present invention also provides the application of the monolayer molybdenum disulfide water-ion separation membrane in seawater desalination, heavy metal nanofiltration, boric acid removal from water, and salt solution separation and purification.
[0015] The monolayer molybdenum disulfide water-ion separation membrane based on grain boundary engineering described in this invention is produced by growing a continuous monolayer MoS2 film on a sapphire α-Al2O3(0001) substrate. All grains in the monolayer MoS2 film exhibit only two lattice orientations: 0° and 60°, with an angle of 60° between them. Mirror twin grain boundaries between adjacent grains are the dominant interface, and defects at the grain boundaries are predominantly 8-4 composite octagonal rings (8-MR), with 8-MR pores accounting for ≥97% of all sieve pores. Ineffective ultra-large pore size defects (>1nm) account for <2.3%. The monolayer MoS2 film is transferred to a supporting substrate material using a PDMS-assisted wet process to form a composite separation membrane.
[0016] The 8-MR pore size is 4.2 Å × 2.4 Å, allowing only a single row of water molecules to pass through, completely trapping hydrated Na. + Cl - Mg 2+ Al 3+ Boric acid molecules, etc.; when water molecules pass through the channels, the number of hydrogen bonds decreases from 3.3 in bulk water to 1.6, the transport activation energy is only 15.1~15.3 kJ / mol, and the osmotic resistance is extremely low.
[0017] The smaller the grain size of the monolayer MoS2 film, the higher the total grain boundary length, and the higher the 8-MR pore density. This is achieved by controlling the average grain area of the monolayer MoS2 film to be between 0.25 and 444.37 μm. 2 The density of 8-MR pores can be controlled within a manageable range. This is especially important when the grain size of the monolayer MoS2 film is 0.25 μm. 2 At that time, the pore density of 8-MR can reach 6.5 × 10⁻⁶. 9 cm -2 .
[0018] In monolayer molybdenum disulfide water-ion separation membranes based on grain boundary engineering, the optimal configuration for MoS2 films is a monolayer structure. Multilayer stacking will significantly reduce water permeation flux due to pore misalignment.
[0019] The separation membrane described in this invention has the following performance requirements: Under forward osmosis conditions, the water permeation flux can reach up to 220 mol·m⁻¹. -2 ・h -1 ・bar -1 The water / sodium chloride selectivity can reach up to 6.5 × 10⁻⁶. 4 Sodium chloride rejection rate > 98%; MgSO4 rejection rate 99% under 13 bar pressure-driven nanofiltration conditions, boron rejection rate 90% in neutral environment, water permeation flux 40 times that of commercial polyamide reverse osmosis membranes; membrane mechanical withstand pressure ≥ 9 MPa, and no significant degradation in rejection performance after 30 days of continuous operation in high-salt simulated seawater.
[0020] The key innovative process in the preparation method described in this invention is as follows: (1) Orientation control core: 750℃ low temperature seed crystal alignment process, high S / Mo ratio ensures that the seed crystal can be rotated and oriented; (2) Pore structure control: 60° oriented grain handrail-type edge splicing, thermodynamically optimal 8-4 composite 8-MR grain boundary (lowest formation energy), replacing the 7-MR ineffective pores generated by random orientation; (3) Pore density control methods: The nucleation density is adjusted by the sulfur source temperature, and the grain size is negatively correlated with the 8-MR pore density; (4) Large area compatibility: The entire CVD process is compatible with 2-inch sapphire wafers, the thin film has a uniform structure throughout the entire area, and the film performance has no positional differences.
[0021] The beneficial effects of this invention are as follows: Breakthrough in sieving performance: 8-MR sub-nanometer pores enable size-based sieving to dominate the separation mechanism, breaking the traditional trade-off between flux and retention in polymer membranes and two-dimensional membranes; grain refinement can simultaneously improve water permeation flux and ion selectivity.
[0022] Highly controllable in fabrication: No post-processing etching / irradiation is required to create holes; precise channels are generated in situ; the pore size is uniform and there are few defects; the two core structural parameters of grain orientation and grain size can be controlled separately through only two steps: sulfur temperature and low temperature alignment.
[0023] High potential for large-scale production: It can prepare large-area continuous monolayer C-MoS2 films with a thickness of 5cm. The composite film has uniform performance after transfer, and there is no performance degradation when the effective film area is increased. The CVD process is compatible with existing mass production lines for two-dimensional materials.
[0024] Broad-spectrum water treatment applications: It can retain monovalent salts, divalent / trivalent metal ions, and boric acid; it is resistant to high-salinity seawater conditions; it can operate stably for 30 days; and its mechanical strength is ≥9 MPa.
[0025] Significant energy consumption advantages: Low water transport activation energy, and water flux is 40 times that of commercial reverse osmosis membranes at the same rejection rate, greatly reducing the energy consumption of water treatment operation. Attached Figure Description
[0026] Figure 1 A is a structural diagram of MoS2 grain boundary defects; B is a molecular dynamics simulation diagram of 7-MR, which is impermeable to water; C is a molecular dynamics simulation diagram of 8-MR, which achieves water sieving and salt ion retention.
[0027] Figure 2 A comparison of the microstructures of randomly oriented R-MoS2 and oriented C-MoS2 films shows that the grain boundaries of C-MoS2 are enriched with 8-MR channels.
[0028] Figure 3 A and B are top views and cross-sectional structures of the composite membrane prepared in this invention, respectively. C is an experimental data graph of water permeation and sodium chloride selective permeation of R-MoS2 prepared in Comparative Example 1 and C-MoS2 with different average grain sizes prepared in Example 1. D is an experimental data graph of sodium chloride selective permeation of C-MoS2 prepared in Example 1 over 30 days. Detailed Implementation
[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0030] The method for preparing a monolayer molybdenum disulfide water-ion separation membrane based on grain boundary engineering according to the present invention includes the following steps: Step 1: Substrate pretreatment and CVD tube furnace zoning. A 2-inch α-Al₂O₃(0001) sapphire wafer was selected as the growth substrate. The tube furnace was divided into a sulfur source temperature zone, a molybdenum source temperature zone, and a thin film growth temperature zone. The carrier gas was high-purity argon, and the entire atmosphere was oxygen-free. The heating temperature of the sulfur source temperature zone was 145~175℃, and the heating temperature of the thin film growth temperature zone was 750~800℃.
[0031] Step 2: Low-temperature seed crystal orientation and alignment, a core orientation control process. The sulfur source temperature zone is raised to 145~175℃, and the film growth temperature zone is raised to 750℃. Molybdenum precursor and sulfur vapor are simultaneously introduced into the film growth temperature zone with an S / Mo atomic ratio >1. MoO3 powder is used as the molybdenum precursor and is introduced into the film growth temperature zone along with argon gas. In the film growth temperature zone, the molybdenum precursor and sulfur vapor react in situ, generating nanoscale MoS2 seed crystals under low nucleation density. The temperature is maintained at 750℃ for 15~40 min, while maintaining a high S / Mo atomic ratio. The small-sized seed crystals have lattice migration ability and spontaneously rotate and align to achieve two stable orientations with the sapphire substrate lattice: 0° or 60°.
[0032] Step 3: Controllable growth of continuous polycrystalline thin films by raising the temperature and adjusting the grain size.
[0033] After seed crystal alignment, the film growth temperature zone is raised to 800℃ and maintained at a constant temperature. The nucleation density is controlled by adjusting the temperature of the sulfur source zone.
[0034] When the temperature of the sulfur source in step 2 is 175℃: the sulfur vapor pressure is high, resulting in a large number of nucleations and an average grain area of 0.25 μm. 2 High 8-MR pore density; When the temperature of the sulfur source in step 2 is 145℃: the sulfur vapor pressure is low, a small number of nuclei form, and the average grain area is 444.37μm. 2 Low 8-MR pore density; The growth time at 800℃ is strictly controlled to be 60~120 min. Insufficient growth time will produce ultra-large non-selective defect pores of 2~7 nm, which will significantly reduce the ion rejection rate. When the growth time is sufficient, the grain handrail-shaped edges are spliced together to form only stable 8-4 composite 8-MR grain boundaries, which will suppress the generation of 12-membered ring high-energy defects.
[0035] Step 4: Wafer-level continuous monolayer MoS2 thin film cooling and collection.
[0036] After growth, the film was naturally cooled to room temperature in an argon atmosphere to obtain a 5 cm diameter, crack-free, uniform and continuous C-MoS2 film with all grains oriented at only 0° / 60° and grain boundaries accounting for ≥97%.
[0037] Step 5: Prepare composite separation membrane by wet transfer of thin film.
[0038] A PDMS elastic stamp is attached to the surface of a MoS2 thin film, and the surface of a sapphire substrate is etched to remove the monolayer MoS2. The MoS2 thin film supported by PDMS is then transferred to a porous polycarbonate PC or alumina anode AAO support substrate, and the PDMS is removed to obtain a crack-free monolayer two-dimensional composite separation membrane.
[0039] To address the micro-pinhole defects inherent in the alumina anode (AAO) substrate, interfacial polymerization is employed for sealing to eliminate non-selective leakage channels. Specifically, the interfacial polymerization sealing process for the substrate composite membrane includes the following steps.
[0040] (5.1) Pretreatment before membrane preparation: Fix the MoS2 / AAO composite membrane after PDMS-assisted transfer to the dead-end filter fixture, ensuring that the single-layer MoS2 functional layer faces upward and the AAO porous substrate faces away; first, introduce isopropanol to wet the AAO pores for 3 minutes, then introduce deionized water to fully replace the organic solvent in the pores, remove the air bubbles in the pores, and drain the free water droplets on the membrane surface at room temperature, leaving only the adsorbed water phase in the AAO pores.
[0041] (5.2) Aqueous phase amine monomer filling: Inject an aqueous solution from the AAO substrate side. The aqueous phase composition is 0.5~2 wt% m-phenylenediamine (MPD) + 0.1 wt% triethylamine (neutralizing agent). The aqueous solution is continuously soaked for 10 min to allow the polyamine monomers to be fully adsorbed and stored in the porous channels of AAO. Take out the composite membrane, hang it vertically for 3 min, and thoroughly wipe off the residual aqueous phase on the surface of MoS2, leaving only the amine monomers inside the channels.
[0042] (5.3) Interfacial polymerization reaction: An organic phase solution was slowly injected into one side of the MoS2 functional layer. The organic phase composition was 0.05~0.2 wt% trimesoyl chloride (TMC) + n-hexane solvent, completely immersing the surface of the MoS2 film and allowing it to stand for 30~60 s. The reaction mechanism is as follows: m-phenylenediamine in the AAO channels diffuses upward along the pinhole defects and crosslinks in situ with the surface trimesoyl chloride inside the pinholes to form a dense polyamide patch; the complete and defect-free 8-MR sub-nanometer sieve channel has a pore size of only 0.42 nm, which amine monomers cannot pass through and will not block the original water transport channels.
[0043] (5.4) Residual liquid cleaning to terminate the reaction: Pour out the organic phase and rinse the surface of MoS2 with pure hexane for 1 min to remove unreacted acyl chloride monomer; then rinse both sides of the membrane with a large amount of deionized water to remove residual free amine in the pores.
[0044] (5.5) Thermosetting crosslinking: The cleaned composite film is placed in an oven at 60~70 ℃ for 8~12 min to promote deep crosslinking of polyamide molecular chains and improve the water pressure resistance and salt resistance stability of the sealing patch.
[0045] (6) Post-treatment: After cooling to room temperature, soak in deionized water for 2 hours to remove uncrosslinked small molecules, complete the sealing, and obtain a C-MoS2 / AAO high-pressure nanofiltration composite membrane with no leakage defects and only retaining 8-MR sieve channels.
[0046] Step 6: Membrane structure post-processing and grain boundary visualization quality inspection.
[0047] Annealing in humid air at 60% relative humidity and 100℃ for 1 hour allows water vapor and hydrocarbon contaminants to accumulate along the grain boundaries. Grain size and grain boundary length can be visually measured using SEM, and 8-MR pore density can be quickly calibrated to achieve batch product quality inspection.
[0048] Omitting the 750℃ low-temperature alignment process in step 2 and directly proceeding to step 3 with a temperature increase to 800℃ will cause the seed crystal to grow rapidly and lose its rotational ability, resulting in a randomly oriented grain film R-MoS2 with grain boundaries dominated by non-permeable seven-membered ring defects 7-MR.
[0049] Figure 1 A is a schematic diagram illustrating the mechanism of selective chloride ion permeation through MoS2 grain boundary defects described in this invention; according to Figure 1 Molecular dynamics simulation diagrams of 7-MR and 8-MR shown in B and C reveal that 7-MR at the MoS2 grain boundaries is impermeable to water, while 8-MR can achieve water sieving and salt ion retention.
[0050] Figure 2 The diagram shows a comparison of the microstructure at grain boundaries in the oriented C-MoS2 film prepared in Example 1 and the randomly oriented R-MoS2 film prepared in Comparative Example 1. The grain boundaries of the oriented C-MoS2 film prepared in Example 1 are handrail-shaped edges joined together, with a grain orientation angle difference of 60° and enriched with 8-MR channels. The grain orientation angle difference of the randomly oriented R-MoS2 film prepared in Comparative Example 1 is 15°, and it is enriched with 7-MR channels.
[0051] Figure 3 Figures A and B show the top view and cross-sectional structure of the composite membrane prepared in this invention, respectively. This invention successfully prepared a composite separation membrane consisting of a single-layer MoS2 thin film. Following the process steps of Example 1, the temperature of the sulfur source was adjusted to control the MoS2 grain size, resulting in an average MoS2 grain size of 444.37 μm. 2 87.3μm 2 7.2μm 2 0.25μm 2 The composite separation membrane was compared with the composite separation membrane prepared in Comparative Example 1 to conduct experiments on water permeation and selective sodium chloride permeation. Figure 3 As shown in Figure C. Under forward osmosis conditions, the water permeation flux can reach up to 220 mol·m⁻². -2 ・h -1 ・bar -1 The water / sodium chloride selectivity can reach up to 6.5 × 10⁻⁶. 4 Sodium chloride retention rate > 99%. Figure 3The graph in Figure D shows the 30-day sodium chloride selective permeation test data of C-MoS2 prepared in Example 1, indicating that the retention performance of the high-salt simulated seawater did not significantly decrease after 30 days of continuous operation.
[0052] The embodiments described above are preferred embodiments of the present invention, but the present invention is not limited to the above embodiments. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essence of the present invention shall fall within the protection scope of the present invention.
[0053] The embodiments described above are preferred embodiments of the present invention, but the present invention is not limited to the above embodiments. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A single-layer molybdenum disulfide water-ion separation membrane based on grain boundary engineering, characterized in that: Including the functional layer and the base layer that are combined together, The functional layer is a continuous monolayer molybdenum disulfide thin film. Within this film, all molybdenum disulfide grains exhibit only two lattice orientations: 0° and 60°, with each grain forming a 60° angle with the others. Adjacent grains form mirror twin grain boundaries, and the dominant defect at these boundaries is an 8-4 composite octagonal ring channel. The substrate layer is a porous membrane material or an anode material, and the continuous monolayer molybdenum disulfide film is attached to the substrate layer by membrane transfer.
2. The monolayer molybdenum disulfide water-ion separation membrane based on grain boundary engineering as described in claim 1, characterized in that, The continuous monolayer molybdenum disulfide film contains 8-membered ring sieve pores that account for ≥97% of all permeable channels, with a pore size of 4.2 Å × 2.4 Å.
3. The monolayer molybdenum disulfide water-ion separation membrane based on grain boundary engineering as described in claim 1, characterized in that, The average grain area of continuous monolayer molybdenum disulfide thin films is controllable within the range of 0.25–444.37 μm. 2 .
4. The monolayer molybdenum disulfide water-ion separation membrane based on grain boundary engineering as described in claim 1, characterized in that, The porous membrane material is an inorganic porous membrane, an organic porous membrane, or an inorganic-organic porous membrane, and the organic porous membrane is preferably a porous polycarbonate.
5. The monolayer molybdenum disulfide water-ion separation membrane based on grain boundary engineering as described in claim 1, characterized in that, The anode material is alumina anode material.
6. A method for preparing the monolayer molybdenum disulfide water-ion separation membrane according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step (1): Substrate pretreatment: α-Al2O3(0001) sapphire wafers were selected as the growth substrate. The tube furnace was divided into a sulfur source temperature zone of 145~175℃ and a thin film growth temperature zone of 750~800℃, with argon gas oxygen-free protection throughout the process. Step (2): Low-temperature seed crystal orientation and alignment: The sulfur source temperature zone is heated to 145~175℃, and the film growth temperature zone is heated to 750℃. MoO3 powder is used as the molybdenum precursor. The sulfur source in the sulfur source temperature zone is introduced into the film growth temperature zone along with argon gas. The S / Mo atomic ratio is >1. In the film growth temperature zone, the molybdenum precursor reacts with sulfur vapor in situ to generate MoS2 nano-seed crystals. The temperature is maintained at 750℃ for 15~40 min, and the high S / Mo atomic ratio is maintained. The MoS2 nano-seed crystals spontaneously rotate and align to 0° or 60° lattice orientation. Step (3): High-temperature continuous film growth: After the MoS2 nanoseed crystals are aligned, the temperature of the sulfur source temperature zone remains unchanged. The film growth temperature zone is heated to 800℃ and kept at a constant temperature for 60~120 min. During the constant temperature growth process, the nucleation density and MoS2 grain size are controlled by adjusting the temperature of the sulfur source temperature zone between 145~175℃. Adjacent grains are spliced together along armrest-shaped edges, forming stable 8-4 composite octagonal ring channels at the grain boundaries; Step (4): Cooling and collecting MoS2 monolayer film: After the reaction is completed, the film is cooled to room temperature under an argon atmosphere to obtain a uniform and continuous monolayer molybdenum disulfide film. Step (5): Wet transfer to prepare composite membrane: Polydimethylsiloxane (PDMS) is used to help peel off the single-layer MoS2 film and transfer it to a porous membrane material or anode material support substrate; when the support substrate is an anode material, the substrate composite membrane is matched with interface polymerization sealing to eliminate pinhole defects and obtain the finished separation membrane.
7. The preparation method according to claim 6, characterized in that, In step (3), the relationship between the sulfur source temperature and the MoS2 grain size is adjusted as follows: when the sulfur source temperature is 175℃, a 0.25 μm grain size is prepared. 2 Small-grained thin films with a thickness of 444.37 μm were prepared when the sulfur source temperature was 145 °C. 2 Large-grain thin films.
8. The preparation method according to claim 6, characterized in that, The anode material mentioned in step (5) is alumina anode (AAO) material, and the specific process for interface polymerization and sealing of the substrate composite film is as follows: (5.1) Pretreatment before membrane preparation: Fix the MoS2 / AAO composite membrane after PDMS-assisted transfer to the dead-end filter fixture, ensuring that the single-layer MoS2 functional layer faces upward and the AAO porous substrate faces away; first, introduce isopropanol to wet the AAO pores, then introduce deionized water to fully replace the organic solvent in the pores, remove air bubbles in the pores, and drain the free water droplets on the membrane surface at room temperature, leaving only the adsorbed aqueous phase in the AAO pores; (5.2) Aqueous phase amine monomer filling: Inject an aqueous solution from the AAO substrate side. The aqueous phase consists of 0.5-2 wt% m-phenylenediamine (MPD) and 0.1 wt% neutralizing agent triethylamine. The aqueous solution is continuously soaked for 10 min to allow the polyamine monomers to be fully adsorbed and stored in the porous channels of the AAO. The composite membrane is then removed, suspended vertically, and the residual aqueous phase on the surface of MoS2 is thoroughly wiped off, leaving only the amine monomers inside the channels. (5.3) Interfacial polymerization reaction: Slowly inject an organic phase solution into one side of the MoS2 functional layer. The organic phase composition is 0.05~0.2 wt% trimesoyl chloride (TMC) and n-hexane solvent, completely immersing the surface of the MoS2 film. Allow the reaction to stand for 30~60s. In the AAO channels, m-phenylenediamine diffuses upward along the pinhole defects and crosslinks in situ with the surface trimesoyl chloride inside the pinholes to form a dense polyamide, thereby sealing the AAO channels. (5.4) Residual liquid washing to terminate the reaction: Pour out the organic phase, and use pure hexane to quickly rinse the surface of MoS2 to remove unreacted acyl chloride monomers; then use a large amount of deionized water to rinse both sides of the membrane to remove residual free amine in the pores; (5.5) Thermosetting crosslinking: The cleaned composite film is placed in an oven at 60~70 ℃ for 8~12 min to promote deep crosslinking of polyamide molecular chains; (6) Post-treatment: After cooling to room temperature, soak in deionized water for 2 h to remove uncrosslinked small molecules, complete the sealing, and obtain a C-MoS2 / AAO high-pressure nanofiltration composite membrane with no leakage defects and only retaining 8-MR sieve channels.
9. The preparation method according to claim 4, characterized in that, It also includes step (6) quality inspection process: the prepared composite membrane is placed in humid and hot air at 60% relative humidity and 100℃ for 1 h for annealing. The pollutants are enriched along the grain boundary. The grain size and grain boundary length are statistically analyzed by scanning electron microscopy, and the octagonal ring pore density is calibrated to achieve batch rapid quality inspection.
10. The application of the single-layer molybdenum disulfide water-ion separation membrane according to claim 1 in seawater desalination, heavy metal nanofiltration, boric acid removal from water, and salt solution separation and purification.
